Developing fluency, metafluency, and comprehension of grade four pupils using modified fluency development lessons - Cidro, Mark Gleen Ocasla (College of Education, University of the Philippines Diliman, 2020)
Studies showed that many fourth graders experienced difficulties in reading due to problems that are foundational in nature. These are underdeveloped word recognition skills, low vocabulary, unexpressive reading, and inadequate comprehension strategies. Thus, an intensive, flexible and foundational reading instruction that addresses these problems is necessary to help them cope with the challenges inherent to this particular grade level. As a response, this study investigated the effects of a 30-sessiono intervention using Modified Fluency Development Lessons originally by Rasinski, Padak, Linek, and Sturtevant (1994) on 36 dysfluent fourth graders fluency, metafluency, and comprehension purposively selected based on a set of criteria. Through the mixed methods design, quantitative and qualitative data were gathered. For the quantitative part, a within-group quasi-experimental design using one-group pretest-posttest design was used. On the other hand, the qualitative part described specific effects of metafluency instruction on the participants metafluency, fluency and comprehension before and after the intervention through case study. The data from observation notes, comprehension outputs, audio recordings, and interview were analyzed to provide more specific information that support the results of statistical tests. Quantitative results showed that the participants accuracy, automaticity, prosody, overall fluency, comprehension, and metafluency performances significantly improved as shown by the t-test results. The qualitative data showed that their oral reading performances and outputs in the post-reading comprehension activities progressed and that they already manifested the awareness of what fluency is and that they started using fix-up strategies when encountering problems in reading orally. With the results of the study in mind, this research concluded that exposing Grade Four students to evidence-based literacy instruction such as the Modified Fluency Development Lessons positively affects development of literacy skills such as comprehension, fluency, and metafluency which are all essential in literacy growth, metafluency skills are important in maximizing fluency skills since the former enables the readers to be more aware of fluency problems and address fluency breakdowns, and fluency, metafluency, and comprehension should develop alongside each other and be given the same attention in literacy instruction. Thus, the study suggests that MFDL be integrated in the fourth-grade classrooms with the concerted efforts of fourth-grade reading teachers, school administrators, and parents as well.